Methods for interference management in medical wireless sensor networks - Abedi, Saied (Array, 2008)
Abstract: Emerging Medical Body Area Networks (MBANs) require new, protected spectrum for clinical applications. This may mean uncoordinated and autonomous operation of multiple MBANs within the new candidate bands. The major question is that how will MBANs coexist as a secondary service with other radio systems? Clinical environment requires balance of robust and efficient wireless techniques to enable coexistence of MBANs and other radio devices where low transmission power MBANs as secondary systems may be vulnerable to interference from incumbent devices transceivers. Physical separation between the MBANs and incumbent radio devices and avoiding the transmission in the same frequency bands among the wireless techniques may be considered. In this paper we propose interference management techniques considering such coexistence between the MBANs and other radio systems. In first part of current paper we introduce a distributed approach for interference management. In second part a centralized gateway controlled solution for mass sensor deployments is proposed to assist the localized distributed interference management described in first part. In third part we deal with the issue of co-existence with primary systems by proposing novel methods for a gateway-to-gateway coordination to assist the methods described in first and second part of this paper